Cross-border portfolio investment and financial integration in Asia and the Pacific region - Sayuri Shirai; Eric Alexander Sugandi (Asian Development Bank Institute (ADBI), 2018)
This paper examines the developments of cross-border portfolio assets and liabilities in the Asia and Pacific region over the periods of 2001-2017. Rapid increases in both portfolio foreign assets and liabilities have taken place particularly after the 2008-2009 global financial crisis. These cross-border portfolio investments have the following characteristics. First, equity has been a dominant source of foreign liabilities notwithstanding efforts to develop bond markets in the region. One exception is Australia, where foreign liabilities have been largely in the form of debt securities. Limited capital inflows to debt securities issued by emerging Asia may be attributable to the early stages of bond market development. Second, in contrast, debt securities have remained dominant as foreign assets held by the region. This mostly reflects Japan's preference toward debt securities. Other Asia and Pacific economies have invested more heavily in foreign equity. Third, the region's assets and liabilities linkages have remained overwhelmingly strengthened against the United States and Europe. Nonetheless, the post-crisis period has witnessed greater financial integration within the region. The intra-regional linkages have been deepest between Hong Kong, China and the People's Republic of China (PRC), where the former has become a major financier of equity issued by the latter. Singapore increasingly plays a role as an equity investor toward the PRC, Japan, ROK, and other ASEAN economies. Albeit from the low level, the intra-ASEAN integration has been noticeable. Fourth, Japan with largest abundant domestic capital has remained predominantly exposed to the United States and Europe. Within the region, debt securities issued by Australia have increasingly attracted Japan's capital. To conclude, intra-regional financial integration has risen at the center of the PRC with growing linkages with Hong Kong, China and Singapore.
Keywords: F36; G15; 330; portfolio investment; financial market integration; Asia and the Pacific